The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/pas.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Granulosa Cell Tumors of the Testis

Abstract: All authors have no conflict of interest to declare. Abstract 2The clinical and pathologic features of 70 juvenile granulosa cell tumors of the testis are presented. The patients were from 30-weeks gestational age to 10 years old; 60 of 67 (90%) whose age is known to us were < 6 months old. Sixty-two underwent gonadectomy, 6 wedge excision, and 2 only biopsy. Twenty-six tumors were left-sided, and 22 right-sided. Six occurred in an undescended testis and 2 in dysgenetic gonads. The most common presentation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…A clinicopathologic study of 70 cases of JGCT performed by Kao et al described 79% of cases with mixed follicular and solid patterns staining positive for inhibin, calretinin, WT1 and FOXL2. AFP staining was uniformly negative except for one case that showed focal reactivity 2 . Our case would be the second one reporting the same AFP positivity in this type of tumor.…”
Section: Discussionsupporting
confidence: 63%
“…A clinicopathologic study of 70 cases of JGCT performed by Kao et al described 79% of cases with mixed follicular and solid patterns staining positive for inhibin, calretinin, WT1 and FOXL2. AFP staining was uniformly negative except for one case that showed focal reactivity 2 . Our case would be the second one reporting the same AFP positivity in this type of tumor.…”
Section: Discussionsupporting
confidence: 63%
“…According to the current World Health Organization (WHO) classification of Tumors of the Urinary System and Male Genital Organs, two histologic subtypes are distinguished: The juvenile tGrCT and the less frequent adult tGrCT (Idrees et al 2017 ). While the juvenile subtype accounts for 6% of all prepubertal testicular tumors and represents the most frequent congenital testicular tumor (Kao et al 2015 ), the adult tGrCT is rare and only reported in small case series and case reports. For both histological subtypes, the risk of metastatic spread is ill defined (Cecchetto et al 2010 ; Mostofi et al 1959 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is frequently diagnosed in the neonatal period; it is uncommon in older children and exceptional in adults. 2 Typical presentation is a painless neonatal scrotal mass 3 ; occasionally it occurs in cryptorchidic testes 3 4 5 or in infants with abnormal karyotypes and ambiguous genitalia 3 ; all cases reported have had a benign outcome. 3 6 Inguinal orchiectomy was invariably considered the treatment of choice but new treatment trends advocate a trans-scrotal approach 7 and testis-sparing surgery where preoperative staging determines that this is safe.…”
Section: Introductionmentioning
confidence: 99%
“…2 Typical presentation is a painless neonatal scrotal mass 3 ; occasionally it occurs in cryptorchidic testes 3 4 5 or in infants with abnormal karyotypes and ambiguous genitalia 3 ; all cases reported have had a benign outcome. 3 6 Inguinal orchiectomy was invariably considered the treatment of choice but new treatment trends advocate a trans-scrotal approach 7 and testis-sparing surgery where preoperative staging determines that this is safe. 6 8 We report a case of JGCT of the testis prenatally diagnosed, an event described only twice in the literature so far, 7 9 followed by inguinal orchiectomy.…”
Section: Introductionmentioning
confidence: 99%